Photoinhibition in cork-oak leaves under stress: influence of the bark-stripping on the chlorophyll fluorescence emission inQuercus suber L. - Werner, Christiane; Correia, O. (Trees-Structure and Function, 1996)
Quercus suber is the primary source for industrial cork and becomes bark-stripped every 9 – 10 years. Recurring cork extraction is a major stress factor and the large water loss from the stripped trunk surface may affect the water balance and tree productivity. To evaluate the effect of bark-stripping, fluorescence emission and stomatal conductance of leaves were determined in groups of barkstripped and control trees. Fv/Fm ratio was found to be significantly lower in bark-stripped trees indicating a reduced photosynthetic efficiency of PSII. Photosynthesis was not found to be stomata limited. The reduction in Fv/Fm resulted from a decline in maximum and variable fluorescence while the initial fluorescence of the darkadapted state (Fo) remained constant. A general decline in photosynthetic efficiency of PSII was found in all trees during the summer, probably reflecting the prolonged environmental stresses during a hot and dry season. Additional stress caused by the bark-stripping seems to enhance the susceptibility to photoinhibition of the trees.
Keywords: bark-stripping; fluorescence emission; Quercus Suber L; water relations

Photoinhibition in cork-oak leaves under stress: influence of the bark-stripping on the chlorophyll fluorescence emission inQuercus suber L. - Werner, Christiane; Correia, O (Trees-Structure and Function, 1996)
Quercus suber is the primary source for industrial cork and becomes bark-stripped every 9 – 10 years. Recurring cork extraction is a major stress factor and the large water loss from the stripped trunk surface may affect the water balance and tree productivity. To evaluate the effect of bark-stripping, fluorescence emission and stomatal conductance of leaves were determined in groups of barkstripped and control trees. Fv/Fm ratio was found to be significantly lower in bark-stripped trees indicating a reduced photosynthetic efficiency of PSII. Photosynthesis was not found to be stomata limited. The reduction in Fv/Fm resulted from a decline in maximum and variable fluorescence while the initial fluorescence of the darkadapted state (Fo) remained constant. A general decline in photosynthetic efficiency of PSII was found in all trees during the summer, probably reflecting the prolonged environmental stresses during a hot and dry season. Additional stress caused by the bark-stripping seems to enhance the susceptibility to photoinhibition of the trees.
Keywords: bark-stripping; fluorescence emission; Quercus Suber L; water relations